2019
DOI: 10.5114/aoms.2019.86794
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sexual dysfunctions and associated risk factors in Poland

Abstract: Introduction: Many biological, psychological and sociocultural factors influence the prevalence of sexual dysfunctions and sexual behavior. The purpose of the study was to evaluate the prevalence of sexual dysfunctions and sexual behaviors. Material and methods: The study was the third edition of a general population-based, cross sectional survey, evaluating sexual attitude, sexual behaviors within and outside relationships and type of sexual dysfunctions present in the Polish population. The survey consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
4
0
2
Order By: Relevance
“…Epidemiological studies in a wider age range, such as that in our study, have shown an initial peak of UI in perimenopause (age 45-54) followed by another increase that begin at age of 70 [28]. In a study with a range of subjects similar to our group, by Nagai et al (age 27-82), the overall prevalence of UI was 19.3% [29]. But even with accurate estimation of menopause timing in longitudinal follow-up studies, these are insufficient to separate the effect of concurrent age-related conditions from the potential contribution of the menopause [28].…”
Section: Discussionsupporting
confidence: 76%
“…Epidemiological studies in a wider age range, such as that in our study, have shown an initial peak of UI in perimenopause (age 45-54) followed by another increase that begin at age of 70 [28]. In a study with a range of subjects similar to our group, by Nagai et al (age 27-82), the overall prevalence of UI was 19.3% [29]. But even with accurate estimation of menopause timing in longitudinal follow-up studies, these are insufficient to separate the effect of concurrent age-related conditions from the potential contribution of the menopause [28].…”
Section: Discussionsupporting
confidence: 76%
“…They experience more often psychological distress, 25% of them suffering from a sexual identity crisis. Psychological support is needed, and a decision of assigned gender is made by the family and medical team [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of research has also shown that SD affects up to 42% of patients with CVDs [ 28 , 29 ], while in general healthy statistics are different. For example, in the Polish population, 40% of women and 36.5% of men reported least one sexual dysfunction [ 30 ]. Also, in Iran, it was found that approximately 31% of women experience sexual dysfunction [ 31 ].…”
Section: Introductionmentioning
confidence: 99%